Modeling and optimizing the thermodynamics of a flat plate solar collector in transient mode for economic purposes - Faouzi Didi; Ebraheem Abdu Musad Saleh; Abhinav Kumar; Ahmed Alawadi; Ali Alsaalamy; Taif Alawsi; Reza Alayi; Hasan Hosseinzadeh; Reza Morovati (AIP Advances, 2024)
This study aims to optimize the economic thermodynamics of a flat plate solar collector and investigate transient heat transfer. This study focuses on modeling and optimization under unfavorable radiation conditions. The method employed here is optimization using a multi-objective genetic algorithm with the assistance of MATLAB software. The key components include objective functions, constraints, and design variables, which are the collector efficiency and the annual total price. The results indicate that increasing the length of the collector has a negative impact on the thermodynamic efficiency and increases the total annual price. Conversely, increasing the width of the collector initially improves the thermodynamic efficiency but then decreases it while also increasing the total annual price. Furthermore, increasing the number of pipes leads to a decrease in the total annual price and an initial increase followed by a decrease in the thermodynamic efficiency. The research was conducted over four different days.